C'est le soleil qui m'a brûlée - Beyala, Calixthe (J'ai lu. Roman, 1988)
"La tête dans les odeurs de l'homme, la bouche contre son sexe, elle se dit qu'il est devenu complètement fou, qu'elle est devenue complètement folle (...). Dans l'état actuel de l'histoire, quoi qu'elle fasse, quoi qu'elle dise, elle aura toujours tort. L'homme c'est lui." Cameroun. Chaleur humide, ciel hypnotique. Dans le bidonville où elle a grandi, abandonnée par sa mère, Ateba cherche avec désespoir sa place dans une société où la femme n'a qu'un droit : se taire. Ecartelée entre plusieurs sentiments contraires, la jeune fille, le ventre en feu, la haine au coeur, est certaine qu'elle peut devenir un jour la plus forte. Incapable de se résoudre à concilier sexe et asservissement, elle refuse de passer sa vie à genoux.--Quatrième de couverture.
Keywords: afrique; afro-féminisme; approches et analyses; arts; cameroun; cours; discipline; féminisme africain; lit2815; premier cycle; roman; régions géographiques; sexisme; systèmes d'oppressions; études littéraires

The rise of a gay and lesbian movement - Adam, Barry D. (Social movements past and present, 1987)
The past decade has seen a wealth of changes in the gay and lesbian movement and a remarkable growth in gay and lesbian studies. In response to this heightened activity Barry D. Adam has updated his 1987 study of the movement to offer a critical reflection on strategies and objectives that have been developed for the protection and welfare of those who love others of their own sex. This revised volume addresses the movement's recovery of momentum in the wake of New Right campaigns and its gains in human rights and domestic partners' legislation in several countries; the impact of AIDS on movement issues and strategies and the renewal of militant tactics through AIDS activism and Queer Nation; internal debates that continually shift the meanings composing homosexual, gay, lesbian, and queer identities and cultures; the proliferation of new movement groups in Eastern Europe, Latin America, Asia, and Africa; and new developments in historical scholarship that are enriching our understanding of same-sex bonding in the past. Adam delineates the formation of gay and lesbian movements as truly a world phenomenon, exploring their histories in the United States, Great Britain, Germany, France, Canada, Scandinavia, Australia, and countries for which very little information about the activities of gay men and lesbians has been made available. In this global picture of the mobilization of homosexuals Adam identifies the critical factors that have given personal and historical subjectivity to desire, that have shaped the faces and territories of homosexual people, and that have generated homophobia and heterosexism. Treating the sociological aspects of the rise of the gay and lesbian movement, Adamalso looks at "new social movements" theory in relation to the gay and lesbian movement and cultural nationalism - whether in the form of cultural feminism or queer nationalism - which he considers an important, perhaps inevitable, moment in the empowerment of inferiorized people.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; activisme; afrique; allemagne; amériques; approches et analyses; asie; canada; cours; discipline; europe; europe de l'est; france; histoire; histoire et politique; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; justice sociale; militance; mobilisation; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; premier cycle; périodes historiques; queer; royaume-uni; régions géographiques; scandinavie; sciences humaines; sex1183; sociologie; systèmes d'oppressions; thématiques; états-unis

Geography of gender in the third world - Momsen, Janet Henshall; Townsend, Janet G. (University of New York Press, 1987)
This pioneering book addresses a key issue in development studies. It follows the influential 'Geography and Gender' as the second collaborative work generated by the Women in Geography Study Groups of the Institute of British Geographers. Its twenty substantive papers explore spatial patterns of gender in Asia, Africa, the caribbean and Latin America. The book's contributors come from Europe, North and South America, India, Sri Lanka, Malaysia, Thailand, Egypt and the Caribbean. 'Geography of Gender in the Third World' analyses the position of women and the societies that ignore and exploit them. it provides both substantial original research and a comprehensive introduction to the geography of gender in low income countries. The book makes a powerful claim for the regional geography of gender.
Keywords: 1900-1999; afrique; amériques; asie; cours; fem1000; genre; identités LGBTQIA2+; premier cycle; périodes historiques; régions géographiques; sud global; thématiques

Lettres parisiennes: histoires d'exil - Huston, Nancy; Sebbar, Leïla (J'ai lu, 1986)
Pendant plus d'un an, deux femmes se sont écrit. L'une est née au Canada anglais, l'autre en Algérie française. A Paris, étrangères en exil, elles ont choisi de travailler, d'aimer, d'avoir des enfants. Elles ne sont ni d'ici, ni de là-bas. Leur pays est celui du verbe. Elle cherchent en tâtonnant ce sentiment d'appartenance qui leur permettrait de réaliser leur destin : celui d'écrivain.--Quatrième de couverture.
Keywords: 1900-1999; afrique; algérie; amériques; arts; canada; cours; discipline; europe; france; immigration; lit3220; littérature; premier cycle; périodes historiques; régions géographiques; thématiques; écriture des femmes*; études littéraires

Feminism and nationalism in the Third World - Jayawardena, Kumari (Zed Books, 1986)
Un texte fondateur du féminisme transnational Depuis vingt-cinq ans, Feminism and Nationalism in the Third World est une introduction essentielle à l'histoire des mouvements de femmes en Asie et au Moyen-Orient à la fin du XIXe et au début du XXe siècle. Dans cette enquête engageante et bien documentée, Kumari Jayawardena présente le féminisme tel qu'il est né dans le Tiers-Monde, émergeant des luttes spécifiques des femmes luttant contre le pouvoir colonial, pour l'éducation ou le vote, pour la sécurité, et contre la pauvreté et les inégalités.
Keywords: 1800-1899; 1900-1999; afrique; approches et analyses; asie; cours; fem1000; féminisme décolonial; féminisme transnational; inégalités; nationalisme; premier cycle; périodes historiques; régions géographiques; sud global; systèmes d'oppressions; théories féministes